Component repair cost functions in Indian context for seismic loss estimation of reinforced concrete buildings. (October 2022) - Aggarwal, Yati; Saha, Sandip Kumar
Abstract: This study proposes component level repair cost functions for efficient estimation of financial losses expected to be incurred due to earthquake-induced damages to typical reinforced concrete (RC) buildings in the Indian context. The proposed repair cost functions account for the variability in the local construction practices and their associated financial implications. Repair cost functions for four drift sensitive building components, i.e., unreinforced masonry walls, reinforced concrete beams, reinforced concrete columns and reinforced concrete beam-column joints, are developed. A detailed case study is presented for three different building configurations commonly observed in the hilly region, i.e., 4-story stepback, 4-story split-foundation, and 4-story regular buildings. The variation in the floor-wise and component-wise repair cost ratio with varying levels of ground motion intensity is investigated. This study also proposes the expected repair cost ratio function for the considered building configurations corresponding to the four building components. It is observed that the expected repair cost ratio is least in 4-story regular building and maximum in 4-story split-foundation building.